Chemical study of the leaves of Lagerstroemia speciosa in Vietnam - Loc, Tran Van; Ngan, Nguyen Thi; Ninh, Pham Thi; Phuong Thao, Tran Thi; Luu, Nguyen Thi; Thu Ha, Le Thi; Thu, Nguyen Minh; Van Anh, Nguyen Thi; Sung, Tran Van (Vietnam Journal of Chemistry, 2015)
The main constituents of the EtOH extract of leaves of Lagerstroemia speciosa supplied by Traphaco company have been quantitatively determined by HPLC to be corosolic acid (2.242 %), asiatic acid (1.219 %) and β-sitosterol. Repeated column chromatography of the n-hexane, ethyl acetate and dichloromethane extract of these leaves led to the isolation of corosolic acid, asiatic acid, quercetin, β-sitosterol and β-sitosterol-3-O-β-D-glucopyranosyl glucoside. The structures of these compounds have been elucidated by the IR, MS and NMR spectral analysis.